2008
DOI: 10.1130/b26111.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of deformation and sedimentation in the northern Sierras Pampeanas: An integrated study of the Neogene Fiambala basin, NW Argentina

Abstract: The thick-skinned Sierras Pampeanas morphotectonic domain of western and northwestern Argentina (27°S-33°S) is characterized by reverse-fault-bounded basement blocks that delimit internally deformed, Neogene sedimentary basins. Forelandbasin evolution in this part of the Andes is still not very well understood. For example, challenging questions exist as to how thickskinned deformation develops, if there are distinct spatiotemporal trends in deformation and exhumation, how such deformation styles infl uence se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 55 publications
3
82
0
Order By: Relevance
“…Jordan et al (2001) and Ramos et al (2002) constrained the ''broken foreland stage'', involving the study region, between 6.5 Ma and present. A similar model was recently proposed by Carrapa et al (2008), who suggested that the transition from thin-skinned to basement thrusting occurred contemporaneously along the Andean foreland (from the Eastern Cordillera in the north to the Bermejo Basin in the south) at ca. 6 Ma.…”
Section: Geologic Settingmentioning
confidence: 65%
“…Jordan et al (2001) and Ramos et al (2002) constrained the ''broken foreland stage'', involving the study region, between 6.5 Ma and present. A similar model was recently proposed by Carrapa et al (2008), who suggested that the transition from thin-skinned to basement thrusting occurred contemporaneously along the Andean foreland (from the Eastern Cordillera in the north to the Bermejo Basin in the south) at ca. 6 Ma.…”
Section: Geologic Settingmentioning
confidence: 65%
“…The study area is situated at ∼25°S, between the arid, internally drained orogenic Puna Plateau in the west and the undeformed Chaco Plain foreland basin in the east. Specifically, this region comprises the southern sectors of the Eastern Cordillera (EC), the Santa Barbara System (SBS), and the Sierras Pampeanas morphotectonic provinces (Figures 1 and 2b); here, we refer to the study area as a whole as the “Salta foreland.” At this latitude the Andean orogen was, until the middle Miocene, bordered by a contiguous foreland basin [e.g., Coutand et al , 2001; Hernández et al , 2005; Carrapa et al , 2008; Bosio et al , 2009]. Since that time, contractile inversion of the Cretaceous Salta Rift [e.g., Baldis et al , 1976; Rolleri , 1976; Bianucci and Homovec , 1982; Salfity , 1982; Allmendinger et al , 1983; Marquillas and Salfity , 1988; Mon and Salfity , 1995; Grier et al , 1991; Viramonte et al , 1999; Kley and Monaldi , 2002; Kley et al , 2005; Carrera et al , 2006; Carrera and Muñoz , 2008] has led to a patchwork of basement‐cored ranges and intervening intermontane basins that have experienced episodes of internal, or reduced external, drainage conditions [e.g., Malamud et al , 1996; Bookhagen et al , 2001; Salfity et al , 2004], but have been recaptured by rivers that are adjusted to the undeformed foreland (Figure 2a).…”
Section: Geologic Settingmentioning
confidence: 99%
“… Reynolds et al , 2000]. The deformation history is only adequately resolved in the arid, well exposed western sector of the foreland, along the eastern flanks of the Puna Plateau [ Salfity et al , 2004; Deeken et al , 2006; Coutand et al , 2006; Hongn et al , 2007; Mortimer et al , 2007; Carrapa et al , 2008; Carrera and Muñoz , 2008; Bosio et al , 2009; Bywater‐Reyes et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The discontinuous nature of deformation within northwestern Argentina has produced spatially disparate and diachronous storage of sediments upstream of the uplifting ranges (Bossi and Palma, 1982;Strecker et al, 1989Strecker et al, , 2009Carrapa et al, 2009). Within basins flanking the margins of the Puna Plateau, conglomerates sourced from the Puna margin and ranges surrounding these basins are sometimes intercalated with lacustrine sediments as well as tephras that constrain the timing of deposition of these sediments.…”
Section: Topographic and Geomorphic Characteristics Of The Eastern Anmentioning
confidence: 99%